Relación entre hormona del crecimiento y diabetes mellitus tipo 1 en población infantil: revisión sistemática - Alvear Castillo, Nicole Adriana (2024)
The Growth Hormone (GH) is a peptide comprised of 191 amino acids, it is produced by somatotropic cells which are found in the adenohypophysis. Its main function is to produce longitudinal growth, this is done by activating insulin-like growth factor type 1 that is located in the liver. On the other hand, type 1 diabetes mellitus (T1DM) is a chronic disease that occurs mostly in children, its main characteristic is the no or little synthesis of insulin due to damage to the beta cells of the pancreas. Growth is one of the most important aspects in the life of an infant, which is badly affected in children with DM1. This paper aims to describe the relationship between growth hormone (GH) and DM1 in children, and also to explain its incidence on the growing process in controlled and uncontrolled patients. The research was performed by means of systematic review, where eligibility criteria were established: articles published from 2014 to the present both in English and Spanish, publications that contributed to achieving the set objectives; of free access, also DeCS (Descriptors in Health Sciences) MeSH (medical subject headings) and Boléan operators (and/or) were used; together with the databases PubMed, Scielo and Lilacs for the extraction of articles, for screening Covidence and Rayyan were used for screening, obtaining a total of 9278 articles, of which 11 were useful to meet the objectives, these data were organised in a PRISMA diagram to finally assess the quality by means of the JBI tool (Joanna Briggs Institute). The results showed that in children with DM1, GH hypersecretion was observed, in addition, in people with optimal glycaemic control growth was mostly normal, in people with suboptimal level growth could be normal or poor, while in uncontrolled people growth was found to be impaired. The hypersecretion of GH occurred due to the lack of insulin, since insulin normally regulates the receptors and postreceptor signalling in the liver, when altered it causes low levels of IGF-1, in turn the decrease of the same causes that there is no negative feedback of the hormone, thus causing elevation of the same. Growth was affected due to the lack of insulin, as this causes low levels of IGF-1, and in some cases, despite the availability of insulin, the deterioration was observed due to different factors such as genetics, inadequate control from the onset of the disease, nutritional status and epigenetics